Comparative study of important parameters of different ZrO2 (Y2O3) ceramics - Csaba Hegedűs; Gábor Balogh; József Gáll; Attila Csík (Hungarian Dental Association, 2019)
Zirconia-based ceramics have been widely applied in the field of prosthodontics. Yttria stabilized tetragonal zirconia polycristal (Y-TZP) can further enhance the bending strength and fracture toughness of prosthesis remarkably by neutralizing the external strain through phase transformation. In this study seven frequently used Y-TZM ceramics were evaluated. Significant differences were found both in the three point bending test and in the fracture toughness results. Also, coherence was found between the monocline-tetracline phase transformation and fracture toughness results of the different ceramics. These parameters are important factors in the final quality of the Y-TZP prosthesis.